2010
DOI: 10.1016/j.trstmh.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss after the first year of stavudine-containing antiretroviral therapy and its association with lipoatrophy, virological failure, adherence and CD4 counts at primary health care level in Kigali, Rwanda

Abstract: CitationWeight loss after the first year of stavudine-containing antiretroviral therapy and its association with lipoatrophy, virological failure, adherence and CD4 counts at primary health care level in Kigali, Rwanda. 2010, 104 (12) a b s t r a c tThis study was conducted among 609 adults on stavudine-based antiretroviral treatment (ART) for at least one year at health center level in Kigali, Rwanda to (a) determine the proportion who manifest weight loss after one year of ART (b) examine the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…Similar findings were recently reported in Ethiopia, which underscores the fact that beyond adherence to an effective ART-regimen, malnutrition remains a threat that deserves special considerations [29]. The fact that weight loss was found in 40% of our participants confirms the uniqueness of HIV infection in inducing a progressive decline of body weight [30,31]. Our data also revealed that about three quarters of participants lived on an average daily ration that range between $2 and $10 per day, and only half of participants could afford 2 meals per day, which in turn justifies the profile of WLP and highlights the financial constraint HIV could have on food insecurity among Cameroonian families [32].…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were recently reported in Ethiopia, which underscores the fact that beyond adherence to an effective ART-regimen, malnutrition remains a threat that deserves special considerations [29]. The fact that weight loss was found in 40% of our participants confirms the uniqueness of HIV infection in inducing a progressive decline of body weight [30,31]. Our data also revealed that about three quarters of participants lived on an average daily ration that range between $2 and $10 per day, and only half of participants could afford 2 meals per day, which in turn justifies the profile of WLP and highlights the financial constraint HIV could have on food insecurity among Cameroonian families [32].…”
Section: Discussionsupporting
confidence: 87%
“…A study from Rwanda also showed that with D4T based ART a high proportion of patients had a progressive decline of body weight in the second year of treatment. 12 There is not enough data available in our study to fully explain this weight loss. There was however a difference in total weight change after 2 years of treatment according to the antiretroviral drugs in the initial regimen, with in the NRTI-category the highest weight gain in patients on a TDF-containing regimen.…”
Section: Discussionmentioning
confidence: 81%
“…This corresponds to the findings of van Griensven et al, who showed that being female, a longer duration of ART, a baseline BMI ≥25 kg/m 2 a D4T-based ART-regimen (compared to an AZT-based regimen), but also (in contrast to our findings) a baseline CD4 cell count ≥150 cells/µL, were significantly associated with lipoatrophy. 12 A South African study showed that lactic acidosis, another consequence of mitochondrial toxicity, was also associated with female gender, increased BMI and D4T therapy. 14 …”
Section: Discussionmentioning
confidence: 99%
“…This likely represents a strong correlation between ART adherence and fat redistribution syndrome, contrary to a previous report from Rwanda. 57 The use of d4T was also associated with VF at baseline when compared to TDF (most commonly used), ZDV, ABC, and ddI. The ART regimen only had a trend towards significance when more variables were included in the model.…”
Section: Discussionmentioning
confidence: 92%